Peningkatan Kreativitas Mahasiswa UIN Palangka Raya Melalui Pembuatan Teh Celup Herbal Fungsional dari Kumis Kucing dan Serai - Nuridah Nuridah; Lestariningsih, Nanik (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service activity aims to enhance the creativity of UIN Palangka Raya students by producing functional herbal tea bags using cat's whiskers (Orthosiphon aristatus) and lemongrass (Cymbopogon citratus). The activity was implemented using a Participatory Action Research (PAR) approach, emphasizing active student participation in all stages of the production process. Participants, third-semester students of the Biology Education Study Program, were introduced to the health benefits of both herbs and were encouraged to practice drying ingredients, weighing formulations, and packaging the products. The results of the activity indicated that students gained a comprehensive understanding of the bioactive compounds in cat's whiskers and lemongrass, proper processing techniques to maintain ingredient quality, and the ideal formulation for making herbal tea bags. Students were also able to produce safe, hygienic, and functional tea bags. This activity has proven effective in enhancing students' knowledge, skills, creativity, and ability to develop innovative products based on local natural ingredients.